Temporal Floodplain Change Assessment Using GIS: A Case of Tinau River, Butwal - Adhikari, Pankaj (International Journal of Environment, 2023)
The understanding of historical floodplain change plays a pivotal role in the minimization of flood risk to communities. Though many research works in Nepal have attempted to study the Land Use Land Cover (LULC) change in different parts of the country, they have not dealt with identification of the floodplain and its change pattern over the period of the time.  This study is aimed at understanding the historical change in floodplain of Tinau River in Butwal city which has repeatedly witnessed devastating flooding events. For the purpose, historical Landsat images for the year 1988, 1999, 2009 and 2020 were acquired from earth explorer site of USGS. The supervised classification was performed in QGIS by classifying into vegetation, agricultural land, water bodies, floodplain and settlement. The result shows that there is significant decrease in the area of the floodplain. In the span of around 32 years, its area has decreased by around 229 hectares. The major regions of floodplain encroachment are found to be Buddhanagar, Majuwa and Sundarnagar. Moreover, significant increase in the area of settlement and decrease in agricultural land was observed. The result could be helpful for the policy makers to formulate strategies to prevent floodplain encroachment and cope with flood risk. Likewise, it can be baseline for further studies which delve into the details of change analysis of floodplain.